2011
DOI: 10.1016/j.jnucmat.2011.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional study of U–Mo and U–Zr alloys

Abstract: Density-functional theory previously used to describe phase equilibria in U-Zr alloys [A.Landa, P. Söderlind, P.E.A. Turchi, J. Alloys Comp. 478 (2009) [103][104][105][106][107][108][109][110] is extended to investigate the ground-state properties of U-Mo solid solutions. We discuss how the heat of formation in both alloys correlates with the charge transfer between the alloy components, and how the specific behavior of the density of states in the vicinity of the Fermi level promotes the stabilization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 53 publications
(40 reference statements)
7
40
2
2
Order By: Relevance
“…Together with our ab initio results obtained previously for U-Mo, U-Am, Pu-U, Pu-Np, and Pu-Am alloys [2,9,11,19,49] these new results will be used to build a thermodynamic database for U-TRU-Mo alloys that are considered to be very promising fuels for fast breeder reactors [4,[50][51][52][53][54][55][56]. …”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Together with our ab initio results obtained previously for U-Mo, U-Am, Pu-U, Pu-Np, and Pu-Am alloys [2,9,11,19,49] these new results will be used to build a thermodynamic database for U-TRU-Mo alloys that are considered to be very promising fuels for fast breeder reactors [4,[50][51][52][53][54][55][56]. …”
Section: Resultsmentioning
confidence: 88%
“…We found that a significantly larger absolute value of the charge transfer from U atoms in the case of the -U-Mo alloys than in the case of the -U-Zr alloys causes the ponderable negative Madelung energy contribution to the heat of formation of the -UMo alloys in comparison with one for the -U-Zr alloys [2]. This difference in the absolute value of the charge transfer from U atoms results in much higher constituent redistribution in -U-Zr than in -U-Mo fuels where a single -phase field exists and can be retained (quenched) as a metastable phase up to room temperature.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…We later expanded our study to the ternary U-Pu-Zr system [16] as well as to the bcc alloys that plutonium forms with MA [17]. In our recent paper [18] we presented results of ab initio calculations of the heat of formation of the -U-Mo solid solutions. In this study we summarize results published in Ref.…”
Section: Introductionmentioning
confidence: 99%